The response of soil microbial community to application of organic amendment to saline land - Cong, Peifei; Huang, Pengfei; Huang, Zhisheng (Frontiers in Microbiology, 2025)
IntroductionThe salinization of coastal soils is a primary cause of global land degradation. The aim of this study was to evaluate the effect of organic amendment on the soil microbial community within a saline gradient.MethodsThe study was designed with five levels of electrical conductivity (EC): 0.33, 0.62, 1.13, 1.45 and 2.04 ds m−1. By conducting indoor potted plant experiments, determine the effects of applying microbial organic fertilizer on the physicochemical properties of soil and the structure of soil microbial communities under different salinity concentrations.ResultsCompared with the control, higher OM content, total N, and higher crop biomass were observed in samples with organic amendment at the same salinity level. At the same salinity levels, the mean bacterial activity (AUC) and the mean number of substrates were higher than in the soil without organic amendment according to analyses by means of Biolog ECO MicroPlate. The results of canonical correspondence analysis indicate that after the application of organic amendments, the composition of loam and clay replaces soil pH, and aboveground biomass replaces root biomass as key indicators closely monitoring Community level physiological profiling (CLPP). In soil with the same salinity level, the application of microbial organic fertilizer led to an increase in the proportion of Actinobacteriota and a decrease in the proportion of Chloroflexi. In 0.3dS m-1 soil, the abundance of actinomycetes increased from 23% to 27% after application of microbial organic fertilizer, while the abundance of basidiomycetes decreased from 20% to 6%. In addition, after the application of microbial organic fertilizer, RB41, blastococcus and solirubrobacter significantly increased, while Melothermus and Herpetosiphon significantly decreased.DiscussionThis study provides a strong theoretical basis for using microbial organic fertilizers to improve saline-alkali soil.